1994
DOI: 10.1007/bf02007774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isolation stress on brain mast cells and brain histamine levels in rats

Abstract: The effects of the chronic social stress of isolation on changes in brain mast cells (MC), the hypothalamic histamine content and the activity of the hypothalamic-pituitary adrenal (HPA) axis were investigated in rats. Social stress of isolation markedly reduced the total number of brain mast cells, most significantly by 90% in the first day. The extent of MC degranulation, 36-67%, in stressed rats did not significantly differ from that in control animals, 45-58%. Isolation stress substantially, though not sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 6 publications
1
16
0
5
Order By: Relevance
“…The possible relationship of mast cells to behavioral states is suggested by the fact that brain mast cell activation can occur in response to isolation stress, 94 to restraint stress, 48 subordination stress, and during courtship after isolation of male doves. 95 The potential pathophysiological role of brain mast cells triggered by acute stress has been reviewed.…”
Section: Significancementioning
confidence: 98%
“…The possible relationship of mast cells to behavioral states is suggested by the fact that brain mast cell activation can occur in response to isolation stress, 94 to restraint stress, 48 subordination stress, and during courtship after isolation of male doves. 95 The potential pathophysiological role of brain mast cells triggered by acute stress has been reviewed.…”
Section: Significancementioning
confidence: 98%
“…Stressed mice had increased inflammatory spinal cord lesions and developed autoimmune antibodies to MBP [299]. Mast cell activation was shown to occur in response to isolation stress [300], restraint stress [278], subordination stress [301], and during courtship following isolation of male doves [302]. …”
Section: Multiple Sclerosismentioning
confidence: 99%
“…An early study by Persinger showed that simple gentle handling of rat pups decreased numbers of mast cells in the brain developmentally, most likely representing an increase in degranulation (25). Psychological stressors induced through social defeat and isolation stress increased the number of mast cells in the brain (26,63). Last, gonadal hormones from conspecifics during mating also increase mast cell number and activation in the brain (23,62,64).…”
Section: Mast Cells Are Active Both Constitutively and Following Stimmentioning
confidence: 99%